Respostas

2014-05-06T22:17:11-03:00
-x² + 6x - 5 = 0
a = -1
b = 6
c = -5
      Δ = b² - 4ac
      Δ = 6² - 4 . (-1) . (-5)
      Δ = 36 - 20
      Δ = 16
              x =  - b ± √Δ 
                         2a
              x =  - 6 ± √16  
                       2 . (-1)
              x' =  - 6 - 4  =  -10  = 5
                         -2         -2
              x'' =  - 6 + 4  =  -2  = 1
                          -2         -2

RESP.: As raízes da equação são 1 e 5

Espero ter ajudado. Valeu!
1 5 1
mt Obg .. me ajudou bastante! fico grata ♥
De nada!